A Wearable Bidirectional Human–Machine Interface: Merging Motion Capture and Vibrotactile Feedback in a Wireless Bracelet - Kindel, Julian; Andreas, Daniel; Hou, Zhongshi; Dwivedi, Anany; Beckerle, Philipp (Multimodal Technologies and Interaction, 2024)
Humans interact with the environment through a variety of senses. Touch in particular contributes to a sense of presence, enhancing perceptual experiences, and establishing causal relations between events. Many human–machine interfaces only allow for one-way communication, which does not do justice to the complexity of the interaction. To address this, we developed a bidirectional human–machine interface featuring a bracelet equipped with linear resonant actuators, controlled via a Robot Operating System (ROS) program, to simulate haptic feedback. Further, the wireless interface includes a motion sensor and a sensor to quantify the tightness of the bracelet. Our functional experiments, which compared stimulation with three and five intensity levels, respectively, were performed by four healthy participants in their twenties and thirties. The participants achieved an average accuracy of 88% estimating three vibration intensity levels. While the estimation accuracy for five intensity levels was only 67%, the results indicated a good performance in perceiving relative vibration changes with an accuracy of 82%. The proposed haptic feedback bracelet will facilitate research investigating the benefits of bidirectional human–machine interfaces and the perception of vibrotactile feedback in general by closing the gap for a versatile device that can provide high-density user feedback in combination with sensors for intent detectio
Keywords: haptic feedback; human–machine interfaces; wireless communication; prototyping